Vision-based Feature matching as a tool for Robotic Localization - Nolasco Amado dos Santos Napoleão (2017)
The algorithms for robotic localization usually rely on calculating the distance based on speed and travel time (odometry). Another categories include template matching and geometric methods such as trilateration and triangulation. These methods however reliable encompass enormous overhead in setup and infrastructure cost. The proposed solution provides a more robust approach to template matching as well as an easier setup.